A Review of Urf on the Distribution of Dapua Coupons During Eid Al-Adha - Rahmi, Lailatul; Ridha, Sofia; Rahmi, Rahmi; Naali, Basri; Andriyaldi, Andriyaldi (Alhurriyah, 2024)
The background of this study is the difference the committee has been chosen as the divider of dapua coupons, will distribute the coupons in the afternoon on the day before the slaughter day, they distribute coupons from one house to another, but in the distribution of dapua coupons there are differences from one house to another, some are given 2 coupons in one family consisting of 3 people,  There are 3 coupons in one family of 5 people and there are given 3 coupons in one family consisting of 7 people. When viewed in terms of habits or 'urf that usually apply in society in general, distributing qurban coupons is distributed equally. In this research method, the author conducted qualitatively, namely research carried out systematically by raising existing data in the field. Where researchers try to find information or sources that can be used as sources of research data at this writing is the head of the qurban, the committee that distributes coupons. To obtain data and material in this writing, the author immediately went to the field to get the desired data in the field by interviewing the source concerned. The results of the study concluded that the system used to distribute dapua coupons was carried out by calculating the number of families or based on KK (family cards), in terms of 'urf or custom is urf shahih, because it is in accordance with Islamic shari'a and brings fame to the community.